Chinese Adolescents’ Perceptions of Aggressive Peers: The Roles of Gender and Cultural Values - Zhang, Linlin (Journal of interpersonal violence, 2023)
Aggression is a prevalent, maladaptive behavioral problem, yet how adolescents view and respond to aggressive peers vary across individual characteristics and cultural contexts. Using a dyadic peer-rating approach, this study investigated adolescents’ perceptions of real-world, rather than hypothetical, aggressive peers, and the role of dyadic gender and individual cultural values. The sample included 274 adolescents (Mage = 13.23 years, SD = 0.68; 52% boys) from two public schools in rural China. Adolescents rated each classmate’s physical and relational aggression, as well as their affiliative preference and social acceptance toward the classmate. Adolescents reported horizontal and vertical individualistic and collectivistic cultural values. Results indicated that (a) adolescents had similarly negative perceptions of physically and relationally aggressive peers; (b) boys and girls had more negative perceptions of male than female physically aggressive peers, and of same-gender than other-gender relationally aggressive peers; and (c) horizontal collectivistic values were associated with more negative, whereas vertical collectivistic and vertical individualistic values were associated with more benign, perceptions of aggressive peers. These findings uncover the complexity of adolescents’ perceptions of aggressive peers and highlight the role of gender and cultural values in understanding attitudes toward aggression in a collectivistic context.